Efficacy and Safety of Ciprofol Alone versus Ciprofol with Fentanyl for Upper Gastrointestinal Endoscopy: A Randomized, Double-Blind, Controlled Trial - Liu L; Li F; Wei Y; Luo L; Shen L; Li J; Sun N; Qian B; Sun D (Drug Design, Development and Therapy)
Lu Liu,1 Feng Li,1 Yanxia Wei,2 Li Luo,1 Li Shen,1 Jie Li,1 Ninglin Sun,1 Bin Qian,1 Dawei Sun3 1Department of Anesthesiology, The First People’s Hospital of Yancheng, Yancheng, Jiangsu, People’s Republic of China; 2Department of Cardiology, The Second Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang, People’s Republic of China; 3Department of Anesthesiology, The Second Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Dawei Sun, Department of Anesthesiology, The Second Affiliated Hospital, Zhejiang University, 88 Jiefang Road, Hangzhou, 310009, People’s Republic of China, Tel +86-19557123453, Email Sundaweide@163.com Bin Qian, Department of Anesthesiology, The First People’s Hospital of Yancheng, 166 Yulong West Road, Yancheng, 224006, People’s Republic of China, Tel +86-13858007629, Email 985578655@qq.comBackground: Ciprofol is increasingly used in surgical procedures, and anesthesiologists have observed that it provides deeper sedation compared to propofol. However, it remains unclear whether the use of ciprofol alone, without combining opioids, is sufficient for upper gastrointestinal endoscopy. This study aims to address this question.Objective: To determine whether ciprofol alone is non-inferior to ciprofol combined with fentanyl regarding sedation success and safety.Methods: In this randomized, double-blind trial, 344 adult patients (ASA I–II, aged 18– 70 years) undergoing elective upper gastrointestinal endoscopy were randomized to receive either ciprofol with saline (CS group) or ciprofol with fentanyl (CF group). Participants in both groups received an initial ciprofol dose of (0.4 mg/kg). The CF group received (1 μg/kg) intravenously before ciprofol administration, while the CS group received an equivalent volume of saline. Additional ciprofol doses (0.15– 0.30 mg/kg) were administered as needed. The primary outcome was sedation success, defined as procedure completion with no more than two additional ciprofol doses within any 5-minute interval. Secondary outcomes included the incidence of hypotension and hypoxemia, as well as adverse events.Results: Sedation success rates were 99.4% for CS and 100% for CF, demonstrating non-inferiority (difference: − 0.6%, 95% CI: − 0.02, 0.01). The CS group had lower respiratory depression rates and better hemodynamic stability but higher intraoperative coughing (18.1% vs 2.9%, P=0.01). Induction and recovery times were slightly longer in the CS group, and postoperative dizziness was more common (15.2% vs 7%, P=0.03).Conclusion: Ciprofol alone is non-inferior to ciprofol with fentanyl for sedation in upper gastrointestinal endoscopy and offers advantages in respiratory and hemodynamic stability. However, it is associated with increased coughing, minor delays in induction and recovery, and more postoperative dizziness.Keywords: ciprofol, upper gastrointestinal endoscopy, sedation, hypotension, hypoxemia, opioid-sparing